PERAN PENGABDIAN KEPADA MASYARAKAT (PKM) DALAM MEWUJUDKAN KASIH YANG MEMULIHKAN DI JEMAAT GMIST EFRATA BUHA - Rifke Alfione Pananggung; Monadeby Wogono (PT. Giat Konseling Nusantara, 2025)
Community Service (PKM) is one of the main pillars of the Tridarma of Higher Education, serving as a bridge between the academic world and the real needs of society. This article aims to examine the role of PKM in realizing